Pembacaan Teks Nashr Hamid Abu Zaid Atas Relasi Laki-Laki dan Perempuan - Rusydi, Muhammad (Muadalah, 2015)
This paper seeks to understand how the reading of text made by Nasr Hamid Abu Zayd, especiallyÂ the problem of relationships between men and women. His work which in directly related toÂ womens problems is DawÃ¢ir al-Khauf. In the book, Abu Zaid had admitted that he wantedÂ to do ijtihÃ¢d solving the women problems. For him the fundamental problem in Islam is text.Â According to him, alquran as a text when revealed has made dialogue with social and culturalÂ around it, especially the Arab community in which the quran was first revealed. The reading ofÂ quran, then, necessitates not only âulÃ»m al-qurâan but also humanities sciences such as semioticsÂ and hermeneutics which could help us to reconstruct the intrinsic values of the quran. On thisÂ method, Abu Zaid has suggested âproductive interpretationâ, qiraâah muntijah, in reading alquran.Â Furthermore, it has been found that alquran is actually very humanizing women, where it isÂ contradictory to the reality and the reading of Islamic texts today.